2007
DOI: 10.1016/j.geomphys.2007.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Spacelike parallels and evolutes in Minkowski pseudo-spheres

Abstract: We consider extrinsic differential geometry on spacelike hypersurfaces in Minkowski pseudo-spheres (hyperbolic space, de Sitter space and the lightcone). In the previous paper [18] we have shown a basic Legendrian duality theorem between pseudo-spheres. We define the spacelike parallels by using the basic Legendrian duality theorem. This definition unifies the notions of parallels of spacelike hypersurfaces in pseudo-spheres. We also define the evolute as the locus of singularities of the spacelike parallels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 23 publications
0
48
0
Order By: Relevance
“…It can be shown that γ, γ = −2 (see [15], or [21] for details on this calculation). Since γ lies in LC * , we have that the position vector γ is a parallel lightlike normal field along γ and so is γ .…”
Section: Lightcone Configurations and Carathéodory Type Conjectures Omentioning
confidence: 99%
See 1 more Smart Citation
“…It can be shown that γ, γ = −2 (see [15], or [21] for details on this calculation). Since γ lies in LC * , we have that the position vector γ is a parallel lightlike normal field along γ and so is γ .…”
Section: Lightcone Configurations and Carathéodory Type Conjectures Omentioning
confidence: 99%
“…In [21] we have defined the notion of the total evolute T E γ of γ : S 1 −→ LC * which is decomposed into T E γ = HE γ ∪ DE γ , where HE γ ⊂ H 2 (−1) and DE γ ⊂ S 2 1 . We have shown that the singularities of the total evolute is corresponding to the flattening points of γ.…”
Section: Then We Have Thatmentioning
confidence: 99%
“…We say that F is a generating family of the graphlike Legendrian unfolding L F (C(F )). We can use all equivalence relations introduced in the previous paper [13,14,15]. Especially, the S.P + -Legendrian equivalence among graphlike Legendrian unfoldings was given in the above contects.…”
Section: Is a Lagrange Stable If And Only If F Is Anmentioning
confidence: 99%
“…On the other hand, singularity theory tools are useful in the investigation of geometric properties of submanifolds immersed in different ambient spaces, from both the local and global viewpoint [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The natural connection between geometry and singularities relies on the basic fact that the contacts of a submanifold with the models (invariant under the action of a suitable transformation group) of the ambient space can be described by means of the analysis of the singularities of appropriate families of contact functions, or equivalently, of their associated Lagrangian and/or Legendrian maps.…”
Section: Introductionmentioning
confidence: 99%